Vascular complications in pediatric renal transplantation during the last 20 years at Santa Casa of São Paulo - Guidoni , Luiz Renato Montez (2005)
Introduction: Vascular complications in immediate or early postoperative with catastrophic consequences are uncommon in renal transplantation. Objective: The aim of the present study was to accomplish a revision of vascular complications in a pediatric population that has undergone renal transplantation in the last 20 years. Methods: A retrospective analysis of 84 children who have undergone renal transplantation at Santa Casa de Sao Paulo between 1985 and 2005 (45 females, 39 males), with age ranging between 1 and 17 years old, being appraised the vascular complications after the transplant. Results: Of a total of 84 patients, 11 (13%) had vascular complications, being 1 (2.3%) with venous thrombosis, 2 (2.3%) with arterial thrombosis, 7 (8.3%) with renal artery stenosis and 1 (1.2%) with rupture of the arterial anastomosis. Conclusion: Vascular complications after pediatric renal transplantation are uncommon events and usually lead to the loss of graft. With regard to the patients with renal artery stenosis, when early diagnosed, was possible to maintain the graft intact after surgical or endoluminal intervention.